2015
DOI: 10.18769/ijasos.94556
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction, Service Quality and the Customer Satisfaction in the It Sector of Karachi

Abstract: This research investigates the relationship between the job satisfaction and the customer satisfaction. Data were collected from 316 employees of IT sector who works for the support contracts and their respective contact persons of the clients they work for. Hence there were 632 respondents in all. Structural Equation Modeling (SEM) was used as the statistical technique. Results indicate that all eight job satisfaction facets studied in the research have significant positive impact on Customer Satisfaction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…This, in turn, is consistent with the previous research (e.g. Ghayas & Hussain, 2015;Ghayas, 2015) where the supervisor's support was argued to be an important ingredient of job satisfaction. This suggests that leadership styles certainly affects employee-level outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This, in turn, is consistent with the previous research (e.g. Ghayas & Hussain, 2015;Ghayas, 2015) where the supervisor's support was argued to be an important ingredient of job satisfaction. This suggests that leadership styles certainly affects employee-level outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Results suggested that continuous learning has a significant association with job satisfaction, this is consistent with the findings of Ghayas and Hussain (2015) where educational enhancement opportunities were used as the dimension of job satisfaction. Therefore, this research arguably paves the way for other researchers to study the learning organizational practices in relation to the other antecedents and consequences of job satisfaction.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations